Post a New Question

re:math

posted by on .

i am having a minor difficulty
i've been stuck for over an hour and don't know what to do
i don't know is this right

? = "+" or "-"
# = number

y=3
(x-3)^2 + (y-4)^2 = 9

i substitute y

(x-3)^2 + (3-4)^2 = 9
(x-3)^2 + 1 = 9
x^2 - 6x + 9 + 1 = 9
x^2 - 6x + 10 = 9
x^2 - 6x + 1 = 0
(x ? #)(x ? #) = 0

i get to here and now i am stuck
can u correct me if i did something wrong

please and thank you

  • re:math - ,

    you are correct.
    Use the quadratic formula

    x= (-b+-sqrt (b^2-4ac))/2a

    or do it this way:

    (x-3)^1+1=9
    (x-3)^2=8= 2*2^2
    take the sqrt of each side
    x-3=+-2*sqrt2

    x= 3+sqrt2 or x=3-sqrt2

  • re:math - ,

    im confused

  • re:math - ,

    Check with your teacher, then.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question